A peroxide sensor for the food and beverages industry - Moody, A. P. (Cranfield University, 2001)
Due to desirable environmental reasons, peroxides have replaced halogenated substances for disinfection purposes in the food and beverage industry. However, cost issues and the requirement to completely remove these agents after disinfection necessitates simple, low-cost and sensitive test methods with a wide dynamic range and on-line capability. The development and performance of such a method is detailed in this thesis. The novelty of this work was in the simplified production of the sensor by pre-mixing all active components before application onto a screen-printed graphite base electrode in a single step. Having established the principle of pre-mixing all the components, the proportions were optimised with regard to a balance between cost and required performance in the industrial application. Once this had been established, the performance and stability was evaluated in the laboratory, a comparative study was performed against other methods for hydrogen peroxide determination and finally the sensor was demonstrated to work in a small-scale industrial field trial. Some of the available mass-production processes for the sensor were considered for suitability and a recommendation made. The relative analytical performances of sensors produced manually and by the recommended process were compared to their visual appearance under a microscope and a possible quality control process suggested for the manufacturing stage. Finally, a scanning electrochemical microscope was commissioned and a method for producing ultramicroelectrodes for use with it developed. This was then used to study the variation of the sensor surface coating with the aim of facilitating the optimisation of the composition, production and quality control processes.